Real time analysis of trace volatile organic compounds in ambient air: a comparison between membrane inlet single photon ionization mass spectrometry and proton transfer reaction mass spectrometry. Issue 35 (26th August 2020) - Yu, Zhujun; Liu, Chao; Niu, Hongzhi; Wu, Manman; Gao, Wei; Zhou, Zhen; Huang, Zhengxu; Li, Xue
Abstract : Membrane single photon ionization mass spectrometry enables real-time monitoring of volatile organic compounds at trace levels, providing important complementary information on aromatics and alkanes in the air. Abstract : Real-time monitoring of volatile organic compounds (VOCs) is critical for a better understanding of chemical processes in ambient air or making minute-by-minute decisions in emergency situations. Proton transfer reaction mass spectrometry (PTR-MS) is nowadays the most commonly used technique for real-time monitoring of VOCs while membrane single photon ionization mass spectrometry (MI-SPI-MS) is a promising MS technique for online detection of trace VOCs. Here, to evaluate the potential of MI-SPI-MS as a complementary tool to PTR-MS, a comprehensive comparison has been performed between MI-SPI-MS and PTR-MS. By using two sets of standard gas mixtures TO15 and PAMS, SPI-MS shows advantages in the detection of ≥C5 alkanes, aromatics and halogens; especially for aromatics, the LODs can reach the ppt level. PTR-MS has performed better in the detection of alkenes, ketones and aldehydes. For outdoor measurements, a number of VOCs have been detected while using MI-SPI-MS and PTR-MS in parallel. Consistent temporal variations have been observed for toluene, C8-aromatics and C9-aromatics by the two instruments, with a more sensitive response from the MI-SPI-MS. Thus by measuring both standard gas mixture and complex ambient air samples, we have successfully demonstrated that MI-SPI-MS will be a helpful tool to provide important complementary information on aromatics and alkanes in air, and proper application of MI-SPI-MS will benefit the real-time monitoring of trace VOCs in relative fields.